2000
DOI: 10.1103/physrevlett.84.1571
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Vortex Plasticity in the Liquid State ofYBa2Cu3O7: Evidence

Abstract: A generalized methodology, based on anisotropic angular dependent magnetoresistance measurements, is presented to deconvolute the contributions to the vortex activation energy (i.e., plastic and pinning energies) in the vortex liquid state of high temperature superconductors. Experimental evidence is given for the appearance of a partially entangled liquid vortex state in YBa 2Cu 3O (7) when random quenched and correlated disorders compete, as in twinned melt textured YBa 2Cu 3O (7) quasisingle crystals with Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 24 publications
3
14
1
Order By: Relevance
“…4,6,10 It was suggested that H lcp was not modified by twin boundaries but this is an unexpected behavior because twin boundaries lead to a secondorder Bose-glass transition, 11 characterized by a cusp in the ''irreversibility line'' and in the vortex activation energy for magnetic-field orientations close to the c axis. 12,13 This behavior would be also inconsistent with a recent study of the influence on H lcp of linear defects created by ion irradiation. 8 That work showed that H lcp is pushed up while the Boseglass regime develops.…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…4,6,10 It was suggested that H lcp was not modified by twin boundaries but this is an unexpected behavior because twin boundaries lead to a secondorder Bose-glass transition, 11 characterized by a cusp in the ''irreversibility line'' and in the vortex activation energy for magnetic-field orientations close to the c axis. 12,13 This behavior would be also inconsistent with a recent study of the influence on H lcp of linear defects created by ion irradiation. 8 That work showed that H lcp is pushed up while the Boseglass regime develops.…”
contrasting
confidence: 76%
“…13,14,22 Considering the fraction of vortices pinned at twin boundaries and that the pinning force only distorts the lattice in one direction, we can estimate the pinning energy per vortex as U tb ϭ1/2nl eff U p , where l eff is the effective length of the vortex pinned at the twin boundary and n is the fraction of vortices pinned at twin boundaries. An upwards shift of H lcp (0) encompasses a decrease of the elastic energy per vortex by the same amount as the increase of pinning energy per vortex at twin boundaries.…”
mentioning
confidence: 99%
“…This situation is recently realized in electron and proton irradiated YBCO single crystal [6,7]. Most recently, although similar phenomenon was predicted in twinned melt-processed Nd-based superconductor [8], a partially entangled vortex state is proposed in melt-processed YBCO with second-phase addition [9]. The competition between the planar, such as TBs, and the quenched disorders such as second-phase, and 0 2 related defects might have dramatic consequence on the enhancement of J, and its optimization in melt-processed NEG material.…”
Section: Introductionsupporting
confidence: 61%
“…Following the 3D anisotropic model, the angular and field dependent activation energy U(,H,T) can be described by 18,19 U͑,H,T ͒ϭU 0 ͑ ,H͒ ͩ 1Ϫ…”
Section: ͑2͒mentioning
confidence: 99%